Quality of benzathine penicillin G: A multinational cross‐sectional study - Robert M. Hand; S. M. D. K. Ganga Senarathna; Madhu Page‐Sharp; Katherine Gray; Dianne Sika‐Paotonu; Meru Sheel; Victor T. G. Chuang; Jorge Martinez; Giuseppe Luna; Laurens Manning; Rosemary Wyber; Jonathan R. Carapetis; et al. (Wiley, 2020)
Abstract Benzathine penicillin G (BPG) is used as first‐line treatment for most forms of syphilis and as secondary prophylaxis against rheumatic heart disease (RHD). Perceptions that poor quality of BPG is linked to reported adverse effects and therapeutic failure may impact syphilis and RHD control programs. Clinical networks and web‐based advertising were used to obtain vials of BPG from a wide range of countries. The quality of BPG was assessed using a high performance liquid chromatography assay capable of detecting relevant impurities and degradation products. Tests for water content, presence of heavy metals and physical characteristics of BPG, including particle size analysis and optical microscopy, also were conducted. Thirty‐five batches of BPG were sourced from 16 countries across 4 WHO regions. All batches passed the US Pharmacopeia requirements for BPG injection (content), with no evidence of breakdown products or other detected contaminants. Water content and heavy metal analysis (n = 11) indicated adherence to regulatory standards and Good Manufacturing Practice. Particle size analysis (n = 20) found two batches with aggregated particles (>400 µm) that were dispersed following sonication. Current batches of BPG were of satisfactory pharmaceutical quality but aggregated particles were found in a modest proportion of samples. Future studies should focus on the physical characteristics of BPG which may contribute to variations in plasma penicillin concentrations an observed needle blockages in clinical practice. Pharmacopeial monographs could be revised to include standards on particle size and crystal morphology of BPG.